The Crambe abyssinica plastome: Brassicaceae phylogenomic analysis, evolution of RNA editing sites, hotspot and microsatellite characterization of the tribe Brassiceae - de Santana Lopes, Amanda; Gomes Pacheco, Túlio; do Nascimento Vieira, Leila; Guerra, Miguel Pedro; Nodari, Rubens Onofre; Maltempi de Souza, Emanuel; de Oliveira Pedrosa, Fábio; Rogalski, Marcelo (Gene, 2018)
Crambe abyssinica is an important oilseed crop that accumulates high levels of erucic acid, which is being recognized as a potential oil platform for several industrial purposes. It belongs to the family Brassicaceae, assigned within the tribe Brassiceae. Both family and tribe have been the subject of several phylogenetic studies, but the relationship between some lineages and genera remains unclear. Here, we report the complete sequencing and characterization of the C. abyssinica plastome. Plastome structure, gene order, and gene content of C. abyssinica are similar to other species of the family Brassicaceae. The only exception is the rps16 gene, which is absent in many genera within the family Brassicaceae, but seems to be functional in the tribe Brassiceae, including C. abyssinica. However, the analysis of gene divergence shows that the rps16 is the most divergent gene in C. abyssinica and within the tribe Brassiceae. In addition, species of the tribe Brassiceae also show similar SSR loci distribution, with some regions containing a high number of SSRs, which are located mainly at the single copy regions. Six hotspots of nucleotide divergence among Brassiceae species were located in the single copy regions by sliding window analysis. Brassicaceae phylogenomic analysis, based on the complete plastomes of 72 taxa, resulted in a well-supported and well-resolved tree. The genus Crambe is positioned within the Brassiceae clade together with the genera Brassica, Raphanus, Sinapis, Cakile, Orychophragmus and Sinalliaria. Moreover, we report several losses and gains of RNA editing sites that occurred in plastomes of Brassiceae species during evolution. •We report the sequencing and characterization of the Crambe abyssinica plastome.•The plastome is 153,771 bp in length and contains 112 unique genes.•Six hotspots of nucleotide divergence among Brassiceae species were characterized.•Our Brassicaceae phylogenomic analysis of 72 taxa resulted in a well-resolved tree.•The tribe Brassiceae shows several events of losses and gains of RNA editing sites.